Hyperpolarization by N-(3-oxododecanoyl)-l-homoserine-lactone, a quorum sensing molecule, in rat thymic lymphocytes. (1st March 2018) - Nishimura-Danjobara, Yumiko; Oyama, Keisuke; Yokoigawa, Kumio; Oyama, Yasuo
Abstract: To study the adverse effects of N-(3-oxododecanoyl)-l -homoserine-lactone (ODHL), a quorum sensing molecule, on mammalian host cells, its effect on membrane potential was examined in rat thymic lymphocytes using flow cytometric techniques with a voltage-sensitive fluorescent probe. As 3–300 μM ODHL elicited hyperpolarization, it is likely that it increases membrane K + permeability because hyperpolarization is directly linked to changing K + gradient across membranes, but not Na + and Cl − gradients. ODHL did not increase intracellular Ca 2+ concentration. ODHL also produced a response in the presence of an intracellular Zn 2+ chelator. Thus, it is unlikely that intracellular Ca 2+ and Zn 2+ are attributed to the response. Quinine, a non-specific K + channel blocker, greatly reduced hyperpolarization. However, because charybdotoxin, tetraethylammonium chloride, 4-aminopyridine, and glibenclamide did not affect it, it is pharmacologically hypothesized that Ca 2+ -activated K + channels, voltage-gated K + channels, and ATP-sensitive K + channels are not involved in ODHL-induced hyperpolarization. Although the K + channels responsible for ODHL-induced hyperpolarization have not been identified, it is suggested that ODHL can elicit hyperpolarization in mammalian host cells, disturbing cellular functions. Highlights: N-(3-Oxododecanoyl)-l -homoserine-lactone (ODHL) is a quorum sensing molecule. ODHL induced hyperpolarization in rat thymic lymphocytes. The hyperpolarization was inhibited by quinine, but not by other K + channel blockers. The hyperpolarization was due to an increase in membrane K + permeability. ODHL may disturb lymphocyte functions via changes in membrane potential.